Designing a model of employee morale in military organizations based on the Grounded Theory - Aliakbar peyvasteh; Hossein Rezayi Bakhtiyari (علوم و فنون نظامی)
Objective: The promotion of happiness and well-being among personnel is of increasing significance in military organizations due to the critical role, value, and impact of human resources. This study aims to design an employee well-being model for military organizations based on grounded theory and to examine its implications for organizational outcomes and the existing body of knowledge in this field.Methodology: This research is applied in nature and employs a qualitative approach using grounded theory methodology. The sampling process was conducted theoretically, utilizing purposive and snowball sampling techniques, and continued until theoretical saturation was achieved. Interviews were conducted with senior experts and professionals within military organizations to ensure comprehensive data collection.Findings: The data analysis process, conducted through open, axial, and selective coding, led to the development of a grounded theory framework for employee well-being in military organizations. The designed model comprises causal, contextual, and intervening conditions, illustrating the central phenomenon, outcomes, and strategic implementation of public policy.Conclusion: Military commanders and human resource policymakers can utilize the findings of this research to enhance employee performance and organizational productivity, foster motivation and job satisfaction, drive organizational growth and development, increase employee resilience and adaptability, strengthen necessary infrastructure, promote future-oriented planning, reduce stress, and enhance team cohesion for improved workforce efficiency. From a theoretical perspective, this study contributes to addressing existing gaps in the literature. Finally, practical recommendations are provided to improve employee well-being in military organizations.